1991
DOI: 10.1016/0378-1097(91)90548-o
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to listeriolysin O reflect the acquired resistance to Listeria monocytogenes in experimentally infected goats

Abstract: We induced experimental listeriosis in goats by two sequential oral inoculations of Listeria monocytogenes serovar 1/2a at 8 months' interval. Immunoblot analysis with the goat sera demonstrated listeriolysin O (LLO) as the principal protein antigen of L. monocytogenes. Pre-existing antibodies to LLO were, depending on their initial level, associated with either mild clinical symptoms of short duration or the total absence of clinical symptoms. Similarly, the presence and development of such antibodies corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 2 publications
2
10
0
Order By: Relevance
“…Our feed prevalence data also suggest that while exposure to L. monocytogenes through contaminated feeds appears to be sufficient to cause listeriosis in small ruminants, clinical listeriosis in cattle may require additional contributing factors (since L. monocytogenes prevalence does not differ between bovine case and control farms). For example, the combination of exposure to particularly virulent L. monocytogenes subtypes and predisposing host factors, such as postpartum immune deficiency or pregnancy, may be required for clinical listeriosis in cattle (2,26).…”
Section: Discussionmentioning
confidence: 99%
“…Our feed prevalence data also suggest that while exposure to L. monocytogenes through contaminated feeds appears to be sufficient to cause listeriosis in small ruminants, clinical listeriosis in cattle may require additional contributing factors (since L. monocytogenes prevalence does not differ between bovine case and control farms). For example, the combination of exposure to particularly virulent L. monocytogenes subtypes and predisposing host factors, such as postpartum immune deficiency or pregnancy, may be required for clinical listeriosis in cattle (2,26).…”
Section: Discussionmentioning
confidence: 99%
“…Although antibodies are not the primary protective mechanism against listeriosis, seroconversion can be demonstrated after acute infection with L. monocytogenes, and antibodies may contribute to protection (16,17,42,43). Serum IgG and IgA were assessed before and after inoculation.…”
Section: Immune Responses (I) Elispot Studiesmentioning
confidence: 99%
“…A murine study showed that oral inoculation of L. monocytogenes expressing HIV-1-gag induced mucosal and systemic immunity to this viral antigen (45). After careful review of available data on oral inoculation of wild-type L. monocytogenes in primates (17) and farm animals, (34,42,43) clinical data available from case series (reviewed in reference 44), and reports of large outbreaks of listeriosis (2, 10, 47), we designed an initial safety study of rationally attenuated L. monocytogenes in adult volunteers.L. monocytogenes organisms are immunostimulatory and lack lipopolysaccharide, and molecularly defined attenuated mutants have been studied in animals.…”
mentioning
confidence: 99%
“…Several studies in human medicine have demonstrated the potential of this toxin as an antigen for the serological diagnosis of listeriosis in humans (6,18). Similar studies have shown that small ruminants develop detectable anti-listeriolysin O antibody titers during L. monocytogenes infections (2,24,25,26,29). Calves orally infected with L. monocytogenes (1,3,4,5) and dairy cows with intramammary L. monocytogenes infections (9, 10, 11) also produce significant humoral responses toward listeriolysin O.…”
mentioning
confidence: 93%